Dexmedetomidine Protects against Ischemia and Reperfusion-Induced Kidney Injury in Rats - Naren Bao; Di Dai (Hindawi Limited, 2020)
Acute kidney injury (AKI), a clinical syndrome, is a sudden onset of kidney failure that severely affects the kidney tubules. One potential treatment is dexmedetomidine (DEX), a highly selective α2-adrenoreceptor agonist that is used as an anesthetic adjuvant. It also has anti-inflammatory, neuroprotective, and sympatholytic qualities. The aim of this study was to establish whether DEX also offers protection against ischemia and reperfusion- (I/R-) induced AKI in rats. An intraperitoneal injection of DEX (25 μg/kg) was administered 30 min prior to the induction of I/R. The results indicate that in the I/R rats, DEX played a protective role by reducing the damage to the tubules and maintaining renal function. Furthermore, in response to I/R, the DEX treatment reduced the mRNA expression of TNF-α, IL-1β, IL-6, and MCP-1 in the kidney tissues and the serum levels of TNF-α, IL-1β, IL-6, and MCP-1. DEX also reduced the levels of oxidative stress and apoptosis in the tubular cells. These results indicate that in response to I/R kidney injury, DEX plays a protective role by inhibiting inflammation and tubular cell apoptosis, reducing the production of reactive oxygen species, and promoting renal function.